2021
DOI: 10.3390/polym13234266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of He and Ar Heat-Assisted Plasma Treatments on the Adhesion Properties of Polytetrafluoroethylene (PTFE)

Abstract: Heat-assisted plasma (HAP) treatment using He gas is known to improve the adhesive-bonding and adhesive-free adhesion properties of polytetrafluoroethylene (PTFE). In this study, we investigated the effects of He and Ar gaseous species on the HAP-treated PTFE surface. Epoxy (EP) adhesive-coated stainless steel (SUS304) and isobutylene–isoprene rubber (IIR) were used as adherents for the evaluation of the adhesive-bonding and adhesive-free adhesion properties of PTFE. In the case of adhesive bonding, the PTFE/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The adhesion strength between pure PTFE and Al plate using an epoxy adhesive increased from 0.02 to 1.4 N/mm via Ar + acrylic acid plasma treatment under atmospheric pressure [31]. In addition, the adhesion strength between pure PTFE and stainless steel bar using an epoxy adhesive increased from 0.00 to 1.17 N/mm via heat-assisted Ar plasma under atmospheric pressure [32]. The direct adhesion between pure PTFE and different materials without any adhesives was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion strength between pure PTFE and Al plate using an epoxy adhesive increased from 0.02 to 1.4 N/mm via Ar + acrylic acid plasma treatment under atmospheric pressure [31]. In addition, the adhesion strength between pure PTFE and stainless steel bar using an epoxy adhesive increased from 0.00 to 1.17 N/mm via heat-assisted Ar plasma under atmospheric pressure [32]. The direct adhesion between pure PTFE and different materials without any adhesives was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can readily damage PTFE structures and cause environmental pollution. As a dry treatment method, plasma treatment is widely used for the surface modification of PTFE, which can introduce a variety of active functional groups on the surface in a short time [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, the wettability after plasma treatment depends on numerous process parameters, such as the type of discharge, feed gas, working pressure, input power, and treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…Among several methods, the chemical wet method [ 14 , 15 , 16 , 17 , 18 ] and the plasma dry method [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] have been mainly studied to increase the water permeability of surfaces coated with fluorine-based polymers. The Vankelecom research team showed improved permeability by modifying the surface of the PVDF-coated membrane through crosslinking with para-xylenediamine (XDA) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Vankelecom research team showed improved permeability by modifying the surface of the PVDF-coated membrane through crosslinking with para-xylenediamine (XDA) [ 26 ]. The Okubo research team improved the adhesion characteristics of PTFE-coated surfaces through a thermal plasma method using He gas [ 24 ]. The chemical wet method has some disadvantages in that the treatment process is complicated and time-consuming [ 27 ].…”
Section: Introductionmentioning
confidence: 99%